What Drives the Trickle-Down Effect of Calling Orientation From Supervisors to Subordinates? The Perspective of Social Learning Theory - Xie, Baoguo; Zhou, Wenxia; Xia, De; Guo, Yongxing (Frontiers in Psychology, 2019)
Despite an increase in research on calling orientation, few studies have examined its antecedents. Drawing on social learning theory, we hypothesized that subordinates’ perceptions of their supervisor’s role modeling mediate the relationship between supervisor’s and subordinates’ calling orientations. Supervisor’s organizational status is supposed to augment the trickle-down process for calling orientation. We used multilevel modeling to test these hypotheses in a sample of 738 employees nested in 77 teams in Chinese enterprises. We found that supervisor’s calling orientation was positively related to subordinate’s calling orientation and that the relationship was fully mediated by subordinates’ perceptions of role modeling. Additionally, supervisor’s organizational status moderated the indirect effect of supervisor’s calling orientation on subordinates’ calling orientation via role modeling. The theoretical and practical implications of the findings are discussed.